From a Patriarchal Orientation to a Relational Justice Model - Sugeng Aminudin; Taufik Hidayat; Abdul Aziz; Afif Faizin; Lukman Hakim (Hikmatuna : Journal for Integrative Islamic Studies, 2026)
This research aims to reconstruct the concept of ḥaḍānah (childcare) by shifting from a patriarchal orientation to a relational justice model from the perspective of fiqh mubādalah. Through the analysis of maṣlaḥah mursalah as the basis for the renewal of Islamic family law, this study addresses the practice of ḥaḍānah in classical fiqh, which tends to be oriented towards a patriarchal structure that hierarchically assigns roles to mother and father. The fiqh mubādalah approach offers a relational paradigm that promotes gender justice by emphasizing the principle of reciprocity (mubādalah) in parenting responsibilities. Through a qualitative method with a normative-philosophical approach, this study examines classical and contemporary fiqh texts and reinterprets the concept of ḥaḍānah based on the principle of maṣlaḥah mursalah, which is contextual and dynamic in Egypt, Morocco, Tunisia, Brunei Darussalam, Malaysia, Saudi Arabia, and Indonesia. The results of the study show that maṣlaḥah mursalah functions as an epistemological instrument to shift the paradigm of Islamic family law toward a relational justice model. This reconstruction emphasizes the importance of rearranging ḥaḍānah norms to be more in line with maqāṣid al-syarī‘ah and modern social realities, while strengthening the position of fiqh as a social ethical system that is adaptive to changing times.